1884. Evaluating SARS-CoV-2 Surveillance Strategies at the United States Naval Academy: A Comparison of Saliva and Dried Blood Spot Serosurveillance Against Molecular-Confirmed Case Detection. (15th December 2022) - Andronescu, Liana R; Richard, Stephanie A; Laing, Eric D; Saperstein, Adam K; Modi, Jitendrakumar; Heaney, Christopher D; Fraser, Jamie A; Shaikh, Saira; Broder, Christopher C; Burgess, Timothy H; Pollett, Simon; Millar, Eugene V; et al.
Abstract: Background: Congregate military populations remain at risk of SARS-CoV-2 outbreaks and the optimal surveillance approach in such settings remains unclear. We enrolled midshipmen at the United States Naval Academy (USNA) in a setting of frequent PCR screening use of prevention strategies. Methods: Dried blood spots (DBS) and saliva were collected in August 2020, December 2020, February 2021 (saliva only) and April/May 2021 to measure anti-SARS-CoV-2 spike (S) and nucleoprotein (NP) IgG. COVID-19 vaccine history and records of SARS-CoV-2 PCR tests and routine asymptomatic screening assays were obtained from the USNA Brigade Medical Clinic. Attack rates were compared with cumulative frequencies of infections. Concordance of saliva and DBS anti-NP and anti-S IgG positivity was determined using Cohen's kappa coefficient. Results: The study enrolled 181 midshipmen. COVID-19 vaccinations were administered in March/April 2021. Samples were collected for 101 participants in August, 73 in December, 57 in February (saliva only), and 63 in April/May. In August, 17 (17%) participants showed evidence of SARS-CoV-2 infection based on anti-S IgG values from DBS and/or saliva. By December 2020, anti-S seroconversion was observed for 5 more based on DBS and/or saliva. By May 2021, 100% of participants were anti-S IgG seropositive after vaccination based on DBS and/or saliva; 48% of participants had seroconverted to anti-NP IgG. Among participants with both DBS and saliva samples, a coefficient of 0.64 showed substantial agreement between anti-S IgG results in August and perfect agreement in December (Table 1). DBS and saliva results for anti-NP IgG were in perfect agreement through December and in substantial agreement in May (0.68, Table 2). Prior to vaccination in March/April 2021, 4/48 of participants had at least one documented SARS-CoV-2 PCR positive result (Table 3). Cumulative PCR test positivity concordance with DBS seroconversion was 37.5% and 60% for anti-S IgG and anti-NP IgG, respectively. Conclusion: There was a substantive SARS-CoV-2 attack rate before vaccination; all vaccinees mounted an anti-S IgG response in blood. We note high agreement between DBS and saliva for IgG measurement. Serology-based surveillance identified substantially more SARS-CoV-2 infections than PCR screening. Disclosures: Jitendrakumar Modi, MD, GlaxoSmithKline: I am a paid speaker for GSK. I do not speak for their flu brand. Timothy H. Burgess, MD, MPH, AstraZeneca: The HJF, in support of the USU IDCRP, was funded to conduct or augment unrelated Phase III Mab and vaccine trials as part of US Govt. COVID19 response Simon Pollett, MBBS, Astra Zeneca: The HJF, in support of the USU IDCRP, was funded to conduct or augment unrelated Phase III Mab and vaccine trials as part of US Govt. COVID19 response Mark P. Simons, PhD, AstraZeneca: The HJF, in support of the USU IDCRP, was funded to conduct or augment unrelated Phase III Mab and vaccine trials as part of US Govt. COVID19 response.